Comprehensive Strategy to Conduct Survey for Improving Response Rate in Halal Supply Chain Management - Mohd Affendi Ahmad Pozin; Rohafiz Sabar; Rohani Abdullah; Rosley Che Ros; Nur Khairiel Anuar (International Journal of Supply Chain Management, 2019)
A research survey has been widely known by many scholars and is very important in data collection; however, it has a real disadvantage of its lower response rate. This is possibly due to incomplete comprehension on how this survey can be made to work effectively especially in supply chain industries that deal with confidentiality and various parties interest. Therefore, this study aims to provide comprehensive strategies that should be conducted to improve response rates. Meeting this aim, this study reviewed studies focusing on strategies to prepare a suggested survey to increase its response rate. Based on an extensive research in literature and local field, the authors found articles considered appropriate to be included in this synthesis. Two strategies were found to improve response rate using a effective survey: designing questionnaire and practical strategies. Designing questionnaire strategy has prominent factors in the beginning steps before sending a questionnaire. The latter is a critical step to get respondents feel that they like to fill a questionnaire. This study contributes to academic literature about how to improve response rate using comprehensive strategies where the previous studies have explained those findings partly.